Analisis Beban Kerja Mental Karyawan Human Resources Development di Aston Banyuwangi Hotel & Conference Center - Hartanti, Leny Istya; Mukti, Masetya; Cardias, Esa Riandy (Universitas Pendidikan Ganesha, 2024)
Aston Banyuwangi Hotel & Conference Center is the first hotel in Banyuwangi under the management of Archipelago International and was established on May 9, 2018. In the Human Resources department at the hotel there is often overtime experienced by employees, so that the work done is less effective and efficient. This is because the work obtained is not in accordance with what is expected so that it will have an impact on the mental state experienced by employees due to the workload they experience. The purpose of this study was to analyze the measurement of mental workload in HRD employees. The research approach used is Mixed Method with Sequential explanatory designs. The results of mental workload measurements from all respondents fall into the